ATTITUDES TOWARDS DEATH AND END-OF-LIFE CARE - Maric, Prof. Dragana (Medical Research, 2023)
End-of-life care represent a particular  and unique segment of palliative care. In the end-of-life period, the task of  involved healthcare professionals is to accompany patients during their last days, weeks or months of life until their death. The way how people die has changed profoundly over the last 70 years. Health  care is now the main context in which many people encounter death. The main focus is on clinical interventions in the end-of-life period with the aim of defeating death, while the broader context and significance of dying is neglected. Progressive medicalization of dying has inevitably led to changing attitudes towards death and dying in both the general population and healthcare professionals. There is a struggle among healthcare professionals and individuals as well to accept the inevitability of death. There has been a growing interest in examining attitudes towards death and dying, in order to achieve greater acceptance of death with repercutions on adequate planning and implementation of end-of-life care. A thorough  understanding and estimation of attitudes about death and dying, both among the general population and among health professionals, is required for the development of an effective strategy to promote end-of-life care. Due to the upcoming examination of attitudes about death and dying in Serbia, as well as exploring their influence on attitudes about end-of-life care, this paper presents current knowledge in this area.
Keywords: dying, death, end-of-life care